Pondok Pesantren dan Resepsi Kolektif Hadis Misoginis - Noviantari, Nicki Kasma; Safri, Edi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This article explores the influence of misogynist hadith texts on islamic boarding school community in Kerinci. The pattern of life in Islamic boarding schools is something phenomenal because it describes their behavior which is based on their understanding of sacred texts such as hadith. However, this behavior is certainly different when viewed from the paradigm of text interpreters, whether textualist or contextualist. This article highlights the dimension which in the context of living hadith is known as collective performation. This research focus on tracing the hadiths that developed in traditional and modern Islamic boarding schools. By using a qualitative method with an ethnographic and gender approach to two types of Islamic boarding schools in Kerinci, the authors found that traditional Islamic boarding schools tended to be textual. They understand the hadith that prohibits women from traveling without a mahram strictly according to its textual meaning. Meanwhile, modern Islamic boarding schools understand this hadith contextually, that safe and secure environmental conditions allow women to leave the house without being accompanied by a mahram. The authors argue that the differences in the meaning of this hadith cannot be separated from the reading sources developed at the Islamic boarding school, as well as the influence of the teaching staff.